2019
DOI: 10.1167/iovs.18-26222
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Ocular Infection in Subretinal Graft Transplantation of iPS Cells-Derived Retinal Pigment Epithelial Cells

Abstract: PURPOSE. To report occurrence of acute severe inflammation after surgical implantation of mycoplasma-infected induced pluripotent stem cell-derived RPE (iPS-RPE) cells into the eyes of healthy primates, and determine the immunopathological mechanisms of the inflammation. METHODS.Ophthalmic allogeneic transplantation of iPS-RPE cells was performed in the subretina of major histocompatibility complex (MHC)-matched (two eyes) and MHCmismatched (one eye) healthy cynomolgus monkeys. The clinical course after transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…3. This echoes recent observations made in the production of preclinical trials batches [28]. In order to mitigate this deviation, it is suggested that postprocess visual microscopic morphological comparison is performed, in this instance 'post-processing' refers to the completion of each process step, i.e.…”
Section: Anticipated and Unexpected Outcomesmentioning
confidence: 53%
“…3. This echoes recent observations made in the production of preclinical trials batches [28]. In order to mitigate this deviation, it is suggested that postprocess visual microscopic morphological comparison is performed, in this instance 'post-processing' refers to the completion of each process step, i.e.…”
Section: Anticipated and Unexpected Outcomesmentioning
confidence: 53%
“…First, we performed lymphocytes-grafts immune reaction (LGIR) tests [19][20][21][22], an in vitro system to predict immune rejection prior to transplantation by coculturing host immune cells and target explant cells. In the current study, for host immune cells, we used peripheral blood mononuclear cells (PBMC) from healthy monkeys (HM-1, -2, -3, and -4), and for target cells, we used human iPSC-RPE cells assuming iPSC-RPE transplantation.…”
Section: Results Of Lgir In Vitro Tests In Monkeysmentioning
confidence: 99%
“…In order to control immune attacks after RPE cell transplantation, we established an in vitro drug assay, termed "drug-lymphocytes-grafts immune reaction (Drug-LGIR)" tests in the current study. Previously, we established a similar test using peripheral blood lymphocytes of the recipient cocultured with iPSC-RPE cells of the explant to predict the immune rejections anticipated after RPE cell transplantation [19][20][21][22]. In the current study, we enhanced the test by applying commonly used medication for ocular inflammatory diseases in Japan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations